No one left behind : good practices to ensure equitable access to water and sanitation in the Pan-European region. (United Nations Economic Commission for Europe : World Health Organization Regional Office for Europe, 2012)
"This publication presents good practices and lessons learned from throughout the pan-European region on the policies and measures to be enacted to provide equitable access to water and sanitation. It distinguishes three key dimensions of equitable access: geographical disparities; specific barriers faced by vulnerable and marginalized groups; and affordability concerns. A range of available policy options to fight inequities in each of those key dimensions are presented."--Page 4 of cover.